COMBINE COMMUNICATIONS OPTICAL NETWORK OF SCADA OF ELECTRIC POWER STATION AND SUBSTATION - A. N. Vasev; R. Sh. Misbakhov; A. I. Ziganshina; V. V. Fedotov (Известия высших учебных заведений: Проблемы энергетики)
The article discusses an economical way to deploy diagnostic monitoring systems for high-voltage electrical units through a combination of passive fiber-optic systems for collecting and transmitting technological information of SCADA with diagnostic information transmission systems of systems for continuous technical diagnostics in them. The usage of existing communication network of SCADA will increase economy and expand the scope of continuous diagnostic systems.